The Era of Coworking: Exploring Corpoworking Practice From The Perspective of Mature Organisation - Setyaningrum, Andina Dwi Kanti (2019)
Coworking spaces and the correlated practice of coworking, have emerged in different forms and various contexts to give spaces to people who work independently while still fulfilling the needs of being a part of a community. Despite the growing interest to explore the coworking space as a research subject, there seems to be a scarce investigation conducted from the corporate sector point of view in regards to coworking. This research revolves around the thought of corporate coworking spaces idea, factors influencing corpoworking space establishment and the operational realities of a coworking space from the perspective of a mature organisation. The result of this study indicates that corpoworking has many resemblances with the “traditional” coworking. Referring to the characteristics of coworking and inversing the four of them (socio-professional, economics, culture, and space) to the company, corpoworking space can be characterised as a shared workplace build up by a corporation for its employees while also welcoming external collaborators, within or outside the company’s premises, which serves as the company’s instrument to embrace innovation and collaboration both internally and externally.